Manifestos and the "two faces" of parties: Addressing both members and voters with one document. (May 2018) - Harmel, Robert; Tan, Alexander C; Janda, Kenneth; Smith, Jason Matthew
It is commonplace to see references to parties' manifestos as their written issue "profiles, " and changes in such documents as constituting changes in the parties' "images" or "identities, " with the latter terms often used interchangeably to capture the role of platforms. This article argues, however, that projection of a party's "image" and its "identity" are two different functions for a manifesto, not just one, and that it is important for the building and testing of theory that this distinction be maintained. Parties are, after all, addressing two audiences simultaneously with one document, and the two dimensions provide two alternative objects of change which can be used strategically to please both audiences at once. The article employs existing manifesto-based measures of parties' relative issue emphases and their positions on a range of issues as indicators of image and identity, respectively, and finds that the two are indeed empirically distinct. Then, an earlier test of the electoral performance hypothesis as applied to emphasis change is replicated with data designed to capture change in issue positions. The test provides evidence for the prudence of maintaining the distinction between emphasis and position as two different dimensions of party profile change.